Mac undercover - Barnett, Mac (Barnett, Mac. Mac B., kid spy ;, 2018)
One day, Mac (smartest boy in his class in a small town in California) receives a telephone call from the Queen of England, recruiting him to find the crown jewels (well, actually just the Coronation Spoon) and so Mac embarks on his first adventure as a secret agent--with the assurance that the Queen will give him a note excusing him from school.